Kontrollierte Studien in der operativen Therapie der obstruktiven Schlafapnoe - Sommer, Ulrich; Maurer, Joachim T.; Hörmann, Karl; Stuck, Boris (HNO, 2012)
The need for surgical treatment alternatives for obstructive sleep apnea is unchanged. However, recommendations regarding these treatments can often only be given with caution as there are only a limited number of controlled studies available. To perform controlled trials and even more so placebo controlled trials in the field of sleep surgery is challenging, especially in comparison to studies evaluating conservative approaches. Nevertheless, these studies can be carried out also in the field of sleep surgery.In this review we present recent concepts and high-quality surgical trials with innovative study designs. A Medline search revealed 310 studies regarding surgical treatment of sleep apnea. These studies were assessed regarding quality, execution and number of subjects. A total of 12 randomized controlled studies were identified addressing palatal implants, radio-frequency surgery, nasal surgery, maxillomandibular advancement and laser-assisted uvulopalatoplasty (LAUP). Furthermore this review addresses the limitations of surgical studies and the differences compared to trials dealing with conservative approaches. The studies presented in this review demonstrate that high-quality trials regarding surgical treatment of obstructive sleep apnea are feasible and can lead to recommendations with high evidence levels.